2004
DOI: 10.1074/jbc.m406532200
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-inducible Expression of the Angiogenic Factor CCN1 in Vascular Smooth Muscle Cells Is Mediated by Egr-1

Abstract: CCN1 is an angiogenic factor that promotes cell adhesion, proliferation, and differentiation. CCN1-deficient mice suffer embryonic death because of vascular defects, demonstrating that CCN1 is required for vessel development. Because mechanical stretch may act as a trigger for vessel development, we investigated the impact of mechanical stretch on the regulatory mechanism of CCN1 expression. Mechanical stretch rapidly enhances CCN1 expression and release in vascular smooth muscle cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 34 publications
2
46
2
Order By: Relevance
“…The gene cyr61, encodes for a matrix-associated cysteine-rich secretory protein, CYR61, also known as CCN-1. CYR61/CCN1 is expressed by fibroblasts in response to TGF-␤ and other growth factors, and is transcriptionally regulated by egr-1 (46). CYR61/CCN1 is associated with fibroblast adhesion, migration, and proliferation; with extracellular matrix remodeling; and with cutaneous wound repair (29,30,(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…The gene cyr61, encodes for a matrix-associated cysteine-rich secretory protein, CYR61, also known as CCN-1. CYR61/CCN1 is expressed by fibroblasts in response to TGF-␤ and other growth factors, and is transcriptionally regulated by egr-1 (46). CYR61/CCN1 is associated with fibroblast adhesion, migration, and proliferation; with extracellular matrix remodeling; and with cutaneous wound repair (29,30,(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular cells such as endothelial cells and smooth muscle cells themselves express CCN1 10 and react to different cardiovascular pathophysiologic settings with augmented CCN1 expression, [18][19][20]26,27 allowing autocrine cell stimulation in terms of tissue regeneration. In contrast, peripheral blood CD34 ϩ cells do not show endogenous CCN1 expression, excluding a mechanism of auto stimulation.…”
Section: Org Frommentioning
confidence: 99%
“…However, the underlying mechanism of cardiovascular regeneration through neovascularization and probably the interaction of different proangiogenic factors remain poorly understood. Upregulated expression of CCN1 accompanies diverse cardiovascular pathophysiologic conditions [18][19][20]27 and percutaneous transluminal coronary angioplasty (PTCA). 28 In particular, smooth muscle cells and cardiomyocytes are a major source of CCN1, suggesting that CCN1 may be a part of an important self-renewal program specifically promoting cardiovascular tissue regeneration.…”
Section: Org Frommentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to play a principal role in osteogenesis by stimulating the migration and differentiation of MSCs into osteoblasts (41,42), and by stimulating proliferation and differentiation of osteoblasts in an integrin and BMP dependent manner (43). The expression of Cyr61/CCN1 is known to be activated in response to mechanical stress at the transcriptional level (6) in several kinds of cells, such as fibroblasts (40), smooth muscle cells (13) in vitro, and skeletal muscle in vivo (20). With regard to bone cells and MSCs, only in vitro studies with shear stress have reported the upregulation of Cyr61/CCN1 (19,21,48).…”
Section: Discussionmentioning
confidence: 99%